2021
DOI: 10.33258/siasat.v6i1.84
|View full text |Cite
|
Sign up to set email alerts
|

Housing Price Index, Wealth, and Protective Shield against Covid-19

Abstract: This paper aims to fill two purposes: 1) we document that housing price index between different cities have inter-correlation. This means that when the housing price in one city goes up the other city follows. However, in the case of a big city and a small city, the housing price index of small city follows the path of housing price index in the small city. 2) The housing price index is a measure of wellbeing and wealth of residents. At the onset of a pandemic, wealthy and richer people have a wealth-protectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The virus hit the American, European and Asian countries harder in terms of reported cases deaths, but Africa suffers more economically and socially due to its fragility (Pichler, Skutnik, Vlad, Shahri, & Ridwan, 2021). Africa, which is the second populous continent after Asia is the most impoverished in terms of poverty, diseases, unemployment, insecurity, weak political institutions, malnutrition and hunger and other indicators of poor standard of living .…”
mentioning
confidence: 99%
“…The virus hit the American, European and Asian countries harder in terms of reported cases deaths, but Africa suffers more economically and socially due to its fragility (Pichler, Skutnik, Vlad, Shahri, & Ridwan, 2021). Africa, which is the second populous continent after Asia is the most impoverished in terms of poverty, diseases, unemployment, insecurity, weak political institutions, malnutrition and hunger and other indicators of poor standard of living .…”
mentioning
confidence: 99%
“…The results of the model indicate a housing price drop of 4.16% in the short-run and 6.49% in the mid-run (late 2020 -early 2021). Subsequent studies [61] used time series analysis and panel data to study housing price indices between different cities have intercorrelation, and compare wealth levels in society to COVID-19 and housing index. This research has shown that higher housing price indexes are associated with lower confirmed cases of COVID-19 and lower risks of death due to the disease.…”
Section: Literature Review With a Discussion Of Resultsmentioning
confidence: 99%